Analysis of the Role of Organizational Commitment as Intervening Variable in the Relationship Between Organizational Citizenship Behavior, Organizational Climate and Teacher Performance - Akhmad Ramli; Singgih Prastawa; Ahmad Muktamar B.; Bashori Bashori; Sudadi Sudadi (Journal on Education, 2023)
The aim of this research is to examine the influence of independent factors (employee behavior and work environment) on the dependent factor (employee efficiency) both separately and together, with employee commitment acting as the mediating factor. The participants for this study were chosen through a saturated sampling method, including the entire population, and consisted of seventy educators. The theoretical framework for this research was evaluated using path analysis methods, considering the previously conducted correlation and regression analyses. The findings of this study indicate that employee conduct has an influence on employee loyalty, workplace atmosphere has an influence on employee loyalty, employee conduct and workplace atmosphere collectively impact employee loyalty, employee conduct has an influence on employee productivity, workplace atmosphere has an influence on employee productivity, employee loyalty has an influence on employee productivity, employee conduct, workplace atmosphere, and employee loyalty collectively influence employee productivity, employee conduct affects employee productivity through employee loyalty, and workplace atmosphere affects employee productivity through employee loyalty.